Marie de France : an analytical bibliography. - Burgess, Glyn S. (Glyn Sheridan) (Research bibliographies & checklists, 2007)
A listing of the latest publications on Marie de France. This is the fourth volume of Marie de France Bibliography, following on from the original volume [1977] and the two Supplements [1986, 1997]. Each volume provides full details of editions and translations of the three works normally attributed to Marie de France [the Lais, the Fables and the Espurgatoire seint Patriz], plus alphabetically arranged lists of books and articles, each accompanied by a substantial summary, and informationon theses and dissertations. GLYN S BURGESS is Emeritus Professor of French at the University of Liverpool.